Răspuns :
Răspuns:
Explicație pas cu pas:
1). 7 x + 4 + 2 ( x - 5)= 8(x+1)
7 x + 4 + 2 x - 10 = 8 x + 8
9 x - 6 = 8 x + 8
9 x - 8 x = 8 + 6
x = 14
___________________________
2).
3(2x+3)+2(3x+2)=9x+4
6x + 9 + 6x+4 = 9 x + 4
12 x + 13 = 9 x + 4
12 x - 9 x = 4 - 13
3 x = - 9
x = ( - 9 ) : 3
x = - 3
_______________________
3)>
- 3 x + 5 + 6 ( - x + 1 ) = - 4 ( x + 6 )
- 3 x + 5 - 6 x + 6 = - 4 x - 24
- 9 x + 11 = - 4 x - 24
- 9 x + 4 x = - 24 - 11
- 5 x = - 35
x = ( - 35 ) : ( - 5 )
x = 7
=== echivalent 1). 7x+4+2(x+1)=8(x+1)=== 7x+4+2x+2= 8x+8=== x= 2
2). 3(2x+3)+2(3x+2)=9x+4=== 6x+9+6x+6=9x+4=== 3x=-11=== x= - 11/3
3). - 3x+5+6(-x+1)=-4(x+6)=== 3x+5-6x+6= - 4x-24=== x=-35